Pemanfaatan Pati Sagu (Metroxylon sago) dan Limbah Kulit Jeruk Sebagai Bioplastik Pembungkus Makanan (Edible Film) Ramah Lingkungan - Nirmala Fitria Firdhausi; Ajeng Ayu Ramadhani; Hawwa’ Cahya Maulida (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
The increasing use of plastic harms the environment because plastic has properties that are difficult to degrade, resulting in environmental pollution, while the demand for plastic is increasing day by day. Bioplastics are a form of innovation from technological developments in modern times. One example of bioplastic is edible film which can function as food packaging that can be consumed. Edible film made from sago starch and orange pectin is believed to be able to produce edible films that have good characteristics. The results of this study, all nine treatment variations did not meet the standards for bioplastics that had been determined by SNI and JIS. The highest tensile strength values were obtained from testing variations in the concentration of 6% sago starch and 2% orange peel pectin (8,643 Mpa), while the highest elongation values were obtained from 4% sago starch and 2% orange peel pectin (5,33%.). Based on the results of the edible film using sago starch and pectin, it showed that more pectin content decrease the biodegradation rate.